EVALUATION OF EXTENDERS FOR CRYOPRESERVATION OF MALABARI BUCK SEMEN - PAWSHE, M; HARSHAN, HM; JOHN, A; KUREIN, MO; SUNANDA (The Indian Journal of Animal Reproduction, 2017)
The efficacy of commercially available Soybean lecithin (Bioxcell) and egg yolk (Triladyl) based extender and lab made Skim milk and Tris based extender was assessed for the cryopreservation of Malabari buck semen. Semen was collected from two bucks and equally divided twenty pooled semen samples were extended using four extenders followed by cryopreservation and storage in liquid nitrogen. Spermatozoa parameters evaluated after initial extension, and at pre-freeze and post-thaw stage revealed better (p<0.05) characteristics at all stages with commercial egg yolk extender in comparison to other extenders. Thus, the commercial egg yolk (Triladyl) based extender is better for cryopreservation of Malabari buck semen.